Role of Jasmonic acid and Nano-fertilizer in the vegetative growth indicators of three cultivars of Rocket Plant (Eruca sativa Mill.) - Hisham Aziz Amran; Jamal Ahmed Abbass Abbass (Kufa Journal for Agricultural Sciences)
The experiment was conducted in the orchards and nurseries development project belonging to Karbala Agriculture Directorate for the two seasons 2020-2021 and 2021-2022 to study the physiological effects of jasmonic acid (JA) and NPK Nano-fertilizer on the vegetative growth indicators of three cultivars of rocket plant (Eruca sativa Mill). The experiment was designed according to the split split plot design using the Randomized Complete Block Design (R.C.B.D). This experiment included 27 treatments from three factors distributed randomly with three replicates (81 experimental units). The first factor represented by three cultivars of rocket plant; (French, Turkish, and the local cultivar) was set up in the main plots. The second factor, NPK nano fertilizer (0, 2, 4) g.L-1 was set up in the subplots, while the third factor comprised three concentrations of jasmonic acid JA (0, 15, 30) mg. L-1 was set up in the sub-subplots. The most important results indicated that spraying with jasmonic acid and nano fertilizer on the three varieties of rocket plants revealed significant differences in the studied indicators. The local cultivar that was sprayed with nano-fertilizer at 4 g.L-1 significantly excelled, and jasmonic acid at 30 mg.L-1 denoted by (V1N2J2) gave the highest results for both seasons compared to plants of the other two cultivars in all indicators of plant vegetative growth. The average plant height was (87.91 and 88.37 cm), number of leaves per plant (28.41 and 28.73 leaves), leaf area(774.67 and 717.57 cm.plant-1), dry weight of vegetative growth(8.53 and 7.43 g.plant-1) and the productivity of leaves (2440.7 and 2328.6 g.m2) for both seasons, respectively. However, the plants of the French cultivar, which were sprayed with distilled water (J0N0V2) recorded the lowest results (55.68 and 55.89 cm) and (13.69 and 13.65 leaves.plant-1), (327.43 and 294.80 cm².plant-1), (5.83 and 5.75 g.plant-1), and (1258.4 and 1136.5 g.m²) for both seasons of the experiment, consecutively.